Religion and the Nigerian state (2019)
One interesting character observed about religion in Nigeria is that it has played both the anabolic and catabolic roles in the society. It has been used as a catalyst for building up as well as instrument for demolishing peaceful coexistence of the citizens of the country. Historical evidences attest to the fact that religious resurgence most especially in the northern part of the country led to violent riots that claimed the lives of more than 100,000 Christians and Muslims within a space of 34 years (1977 and 2011). From examination carried out on the perennial incidence of religio-political crises in Nigeria, factors responsible include the missionary spirit of the Christian faith which the Muslims could not tolerate; persistent attempts to nationalize sectional interest; the surreptitious use of religion by the government to achieve economic or political advantages and the reluctance to accept a change in certain areas. Having considered the effects of religious crises on the psyche of the citizens, the paper recommends that Nigerians must come to terms with the religious plurality of the country and the imperatives of secularity. Harmonious coexistence demands sacrifice from various religious groups within the state while attitudinal re-engineering is recommended at all levels of religious and political leadership. The expectation of humans to live in a world that is peaceful has been a mirage because of their failure to recognise the nexus between justice and peace. It is no doubt that the concept of peace has taken central position in global conferences- political, economic or religious, yet, it seems people have only been paying lip-service to its realisation. Also, they fail to adequately address gender inequality, dehumanizing attitude of some stronger nations towards the weaker ones, and more significantly, the trending issue of the destruction of non-human creatures by humans. These factors among many others have orchestrated the tension that is being experienced in the cosmic order. This paper therefore advocates for mutual respect among humans irrespective of gender or race and responsible earth stewardship, especially by all Africans, so as to achieve peace in the society. Special emphasis has been placed on eco-justice considering its far-reaching significance to the restoration of peace. Sociological approach was adopted in gathering data that cut across many disciplines.